Harnessing the potential of transverse thin cell layer culture for high-frequency micropropagation of Thai ginseng (Kaempferia parviflora Wall. Ex Baker) - Koh, Khong Shien; Ismail, Mohd Firdaus; Naharudin, Nazatul Shima; Gantait, Saikat; Sinniah, Uma Rani (Elsevier, 2024)
In vitro plant propagation techniques play an important role in modern agriculture and horticulture, offering efficient methods for the accelerated multiplication of high-value plant species. Thin cell layer (TCL) culture technique has emerged as a promising approach for large-scale in vitro plantlets production. This study explores the potential of TCL culture as a cutting-edge strategy to enhance the efficiency of multiple shoots formation in Kaempferia parviflora. An attempt was also made to look into the synergistic effects of cytokinin and auxin [6-benzyladenine (BA) - indole-3-acetic acid (IAA)] during micropropagation. Shoot tip explants (from rhizome sprouts) were cultured onto Murashige and Skoog (MS) medium enriched with BA (2.0–8.0 mg/L) and IAA (0.2–0.8 mg/L) in combination where the highest shoot number (7.3 shoots/explant) and length (5.9 cm) was obtained in 8.0 mg/L BA and 0.8 mg/L IAA. Subsequently, the transverse thin cell layer (tTCL) culture system was successfully utilized whereby the shoot tip explants were individually sliced from tips at the meristem and cultured onto MS medium supplemented with BA (2.0–8.0 mg/L) and IAA (0.2–0.8 mg/L) in combination. The regenerated tTCLs exhibited the highest shoot multiplication (9.3 shoots/tTCL; 28 shoots/shoot tip) and length (5.3 cm) in 4.0 mg/L BA + 0.8 mg/L IAA, thus significantly increased number of plantlets were obtained from tTCL culture (953.0 plantlets) compared to shoot tip culture (527.7 plantlets) after six sub-culture cycles. The tTCL regenerants were successfully acclimatized (with 90% survival) and displayed active growth. Genetic fidelity assessment via inter-simple sequence repeats, conserved DNA-derived polymorphism, directed amplification of minisatellite-region DNA, and start codon targeted polymorphism marker systems suggested that a very low level (5.8%; 148 out of 2572 scorable bands) of polymorphism was detected whereas the ploidy level remained unchanged, confirmed by flow cytometry analysis. The implementation of tTCL culture, coupled with a controlled sub-culture regimen, holds significant potential for the efficient commercial-scale production of K. parviflora.